2022
DOI: 10.5005/jp-journals-10071-24372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Predictors, Kinetics of Renal Recovery and Outcomes of COVID-19 Patients with Acute Kidney Injury Admitted to Intensive Care Unit: An Observational Study

Abstract: A bstract Background The incidence of acute kidney injury (AKI) is greater than 50% among coronavirus disease-2019 (COVID-19) patients admitted to the intensive care unit (ICU). However, the literature on predictors and kinetics of renal recovery remains unclear. Patients and methods This observational study was conducted in a 30-bedded mixed ICU of a tertiary care center from May 2020 to July 2021. A total of 200 consecutive adult COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The incidence rate of acute kidney injury (AKI) can reach 41% to 62% [ 6 9 ] in patients with COVID-19. Despite the high incidence of AKI, research has revealed that the majority of patients can recover within the first week (the median number of days to recover from AKI is 6) following infection [ 10 ]. Studies also suggest that patients with COVID-19 with longer AKI recovery times have a higher incidence of chronic kidney disease (CKD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of acute kidney injury (AKI) can reach 41% to 62% [ 6 9 ] in patients with COVID-19. Despite the high incidence of AKI, research has revealed that the majority of patients can recover within the first week (the median number of days to recover from AKI is 6) following infection [ 10 ]. Studies also suggest that patients with COVID-19 with longer AKI recovery times have a higher incidence of chronic kidney disease (CKD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ]. At the same time, COV-AKI has been shown to be a predictor of mortality [ 8 ] and for survivors, renal recovery varies according to the operational definition used in different studies, but remains lower when compared with other causes of AKI [ 9 ]. AKI was found to be also a predictor for readmission and mortality in COVID-19 patients discharged early from the hospital [ 10 ].…”
Section: Introductionmentioning
confidence: 99%